(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Job satisfaction is an extremely and systematically investigated work related attitude and is generally defined by the theorist. Job Satisfaction is correlated positively with employee productivity and then negatively with employee turnover. The reliable seeking ways or techniques to actively promote the job satisfaction among employees might have the optimistic societal consequences in the form of enhanced well-being of employees and their family. There are abundant studies to explore the sources of job satisfaction. Job satisfaction is a very important attribute which is frequently measured by organizations. The most common way of measurement is the use of rating scales where employees report their reactions to their jobs. Questions relate to rate of pay, work responsibilities, variety of tasks, promotional opportunities, the work itself and co-workers. 120 Samples were selected for this study.